IMPLEMENTASI MANAJEMEN KONFLIK MELALUI SISTEM PENJAMINAN MUTU PADA PANDEMI DI SDI AL HUDA KOTA KEDIRI - Khafidhotun Nasikhah; Sulistyorini (Journal Khafi : Journal Of Islamic Studies, 2023)
This study aims to determine the implementation of SDI Al Huda conflict management through quality assurance, especially during the covid-19 pandemic. Al Huda, who was able to survive even during the pandemic, is even now experiencing growth from the acquisition of a total number of students with a total of 496. Through interviews with school principals during a pandemic with online learning, Al Huda often comes into contact with conflicts, especially the relationship with parents. This study concludes SDI Al Huda Kediri City has implemented conflict management and strategies within the organization. using a five-step strategy to achieve peace in conflict, a step that is as basic as that proposed by Stevenin. The conflict management model used by SDI Al Huda can be said to use an integrative model of organizational conflict management. with a formula that includes: 1.) rationale 2.) expected impact 3.) sources of conflict 4.) conflict management in increasing organizational productivity